Restoration of Watersheds Under Forest Area Use Permits: Insights from PT. Dempo Sumber Energi Reforestation Program - Amini, Aisyah; Frinaldi, Aldri; Lanin, Dasman; Rembrandt, Rembrandt (Postgraduate School, Universitas Negeri Padang, 2024)
This research aims to assess efforts in restoring watersheds through the implementation of forest area use permits, with a specific focus on PT. Dempo Sumber Energi reforestation program in Nagari Palangai Kaciak, Pesisir Selatan Regency. A normative legal methodology combined with conceptual analysis was employed, using primary legal references such as Government Regulation No. 26/2020 on Reforestation and Restoration and Minister of Environment and Forestry Regulation No. P.59/MENLHK/SETJEN/KUM.1/10/2019. The study revealed that PT. Dempo Sumber Energi rehabilitated 67 hectares of the watershed through intensive reforestation efforts, planting 625 seedlings each hectare. The land preparation involved clearing and planting activities using strip and contour techniques, adapted to the terrain's topography. Two reforestation strategies were applied: intercropping and buffer zone planting, which were selected to enhance compatibility with local conditions. The findings underline the significance of regulated and systematic planting practices in restoring watershed functionality, reducing environmental risks, and promoting sustainable land management. The initiative not only supports environmental conservation but also complies with legal mandates requiring collaboration between government agencies and private sectors. In conclusion, well-structured reforestation strategies, backed by clear legal frameworks, are crucial for achieving watershed restoration goals and fostering ecological resilience.